Implementation of the Pictographic Communication System in a Population with Cerebral Palsy: A Case Report - Palacios Lenis, Jennifer; Bonilla Villegas, Daniela; Rodríguez Campos, Daniela; Ortega Ledesma, María Fernanda; Argüello-Vélez, Patricia (Revista de Investigación en Logopedia, 2022)
Cerebral palsy (CP) is defined as one of the non-progressive neurological disorders that can be caused by lesions or abnormalities in the immature or developing brain. Cerebral palsy of spastic type, concomit with motor and language disorders, altering the processes of message transmission during communication. In response to these alterations at the communicative level, Augmentativeand Alternative Communication Systems (AACS) are created, tools that allow interaction with the environment, either complementing oral emissions or replacing them with symbols, written words, digital readers, among others. The objective of this research is to implement an alternative communication system in an athlete with cerebral palsy, through the use of the Let Me Talk® application. It begins with an evaluation using the Barcelona Test as an instrument for the identification of communication and language skills. The adaptation process of the Pictographic Communication System was developed in 10 sessions, in which the athlete participated through the use of the application; the sessions were recorded in a self-authored participant observation format. In the analysis of the results, it is concluded that the implemented SAAC allowed the athlete to participate during the proposed conversations, structuring simple andcomplex sentences with the use of grammatical categories and inflections, and the execution of mobilizing questions complemented by non-verbal expressions, which favored independent participation in communicative situations.
Keywords: Alternative communication systems; Cerebral palsy; Communication